The basics of financial econometrics : tools, concepts, and asset management applications - Fabozzi, Frank J. (Hoboken, New Jersey : John Wiley & Sons, Inc., 2014)
"An accessible guide to the growing field of financial econometrics ."--Provided by publisher.
Simple Linear Regression -- Multiple Linear Regression -- Building and Testing a Multiple Linear Regression Model -- Introduction to Time Series Analysis -- Regression Models with Categorical Variables -- Quantile Regressions -- Robust Regressions -- Autoregressive Moving Average Models -- Cointegration -- Autoregressive Heteroscedasticity Model and Its Variants -- Factor Analysis and Principal Components Analysis -- Model Estimation -- Model Selection -- Formulating and Implementing Investment Strategies Using Financial Econometrics -- Appendix A: Descriptive Statistics -- Appendix B: Continuous Probability Distributions Commonly Used in Financial Econometrics -- Appendix C: Inferential Statistics -- Appendix D: Fundamentals of Matrix Algebra -- Appendix E: Model Selection Criterion: AIC and BIC -- Appendix F: Robust Statistics.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Finance -- Econometric models; Econometrics; Finance -- Mathematical models; Finance; Financial risk management; BUSINESS & ECONOMICS -- Economics -- General; BUSINESS & ECONOMICS -- Reference; Econometrics; Finance -- Econometric models; Electronic books